Secure PHP development : building 50 practical applications - Mohammed J. Kabir (Mc Graw Hill, 2003)
This is not a PHP language book for use as referensce. There are many good PHP language books out there. This book is designed for intermediate-to advanced-level PHP developers who can review the fifty PHP applications developed for this book and deploy them as is or customize as needed. However, it is entirely possible for someone with very little PHP background to deploy the applications developed for this book. Therefore, even if you are not currently a PHP developer, you can make use of all the applications with very little configuration changes.